APPLICATION OF LEADERSHIP AND ENTREPRENEURSHIP AND THEIR INFLUENCE IN THE HOSPITAL ENVIRONMENT - Juliana, Dewi Sri; Ratnawati, Yeni; Widjaja, Yani Restiani; Purwadhi (International Journal Multidisciplinary (IJMI), 2024)
Abstract— Health care operates within a complex and dynamic environment, particularly in the context of hospital care in Indonesia. General Background: The effectiveness of an organization in this sector is influenced by various factors, necessitating continuous improvement in innovation to foster growth and adaptability. Specific Background: Leadership plays a crucial role in guiding organizations toward achieving their vision and mission, especially in a landscape marked by financial constraints, resource shortages, and heightened competition. Knowledge Gap: Despite the recognized importance of entrepreneurial principles in enhancing innovative work behavior, there is limited empirical research focusing on their application within Indonesian hospitals. Aims: This study aims to investigate the impact of entrepreneurial leadership on fostering innovation in hospital settings, with a specific focus on its effects on organizational performance and adaptability. Results: Preliminary findings suggest that integrating entrepreneurial practices not only enhances innovative behaviors among healthcare professionals but also improves overall organizational effectiveness. Novelty: This research contributes to the existing literature by demonstrating how entrepreneurial leadership can serve as a catalyst for innovation in a challenging health care environment. Implications: The results underline the necessity for hospital leaders to embrace entrepreneurial approaches to navigate the complexities of the health care sector, thereby ensuring the delivery of high-quality services and maintaining competitive advantage.